(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents the study of milk productivity of karakul sheep depending on the colour in the northern conditions of the Republic of Karakalpakstan. Optimal opportunities of increasing мeat productivity were determined; the results of changing daily milk productivity in agedependent dynamics weregiven